Estimation of stature from hand measurements in Thais - Suda Riengrojpitak, Piti Laulathaphol, Montip Tiensuwan (Journal of Food Health and Bioenvironmental Science, 2015)
Abstract Identification of an unknown individual is one of the main objectives of forensic investigations. Estimation of stature from human remains is particularly important in establishing positive personal identification. The estimated stature can be used to narrow down the pool of potential matching identities in the missing persons reports. To date, regression equations for estimation of stature from hand measurements are not yet available for the Thai population. Therefore, the present study aims to investigate the relationship between stature and hand measurements in Thais and derive regression equations for estimation of stature from hand measurements for Thais. Stature, hand length, hand width, and palm length were taken from a study sample consisting of 100 randomly selected Thai students (50 males and 50 females) from Faculty of Science, Mahidol University, Thailand, with ages ranging from 18 to 26 years. Correlation and regression analyses were performed on the measurement data. All the hand measurements of both sexes exhibit positive and statistically significant correlation coefficients (r) with stature (r = 0.349-0.736, p < 0.05). The regression equations show a standard error of the estimate (SEE) ranging from ±3.295 cm to ±4.878 cm. Simple linear equations using only the hand length provide the lowest SEE for both sexes (SEE ±3.295-3.722 cm), making hand length one of the best measurements for stature estimation. Keywords: estimation of stature, hand measurements, Thais